Biossistemática do complexo Vellozia hirsuta (Velloziaceae) baseada em análise filogeográfica e genética de populações - Ariane Raquel Barbosa (2011)
The campos rupestres of the Espinhaço Range are known for their richness of plant species with a high degree of endemism, cited as a result of disjunctions in the distribution of populations due to the discontinuity of the mountain ranges. This disjunction has been cited as a major factor responsible for the isolation and differentiation of populations. Vellozia hirsuta (Velloziaceae) corresponds to a species complex that occurs in the Espinhaço Range and shows great variation in external morphology and leaf anatomy. This variation led to synonymization of four species under the name V. hirsuta and the recognition of 14 morpho-anatomical patterns. In this study we investigated the correlation of those morphological and anatomical patterns with the distribution of genetic variability and geographic distribution of populations, also investigating the possible existence of barriers responsible for the restriction of recent or historical gene flow among populations. Using sequencing of trnL-rpl32F intergenic region (cpDNA), the occurrence of 25 polymorphic sites revealed 20 haplotypes in the 23 populations sampled. The populations of V. hirsuta appears structured (ST = 0.818) in four phylogeographic groups that correspond to major geographic regions occupied by the species, demonstrating a geographic structure of genetic diversity and lack of correlation with the morpho-anatomical patterns described. The group formed by the populations of northern Minas Gerais and southern Bahia states was genetically more divergent due to the presence of unique haplotypes within their populations. This result associated with geographic isolation and morphological differentiation suggests that this group could be recognized as a taxon distinct from other populations of V. hirsuta. In the study of population genetics performed with ISSR, the mean heterozygosity of the populations (0.216) showed lower values than species of similar biological characteristics. The AMOVA showed high variation within (84-86%) and low divergence (11-14%) among populations. The Bayesian analysis showed a number of populations genetically structured with no precise boundaries between these groups, but instead structured in a north-south geographical gradient. However, the northern group appears to be more differentiated than others and delimitation of this group as a distinct taxon is supported, as found in the phylogeographical analysis. Both phylogeographical and population genetics did not support the recognition of any taxa synonymized under V. hirsuta. Therefore, V. hirsuta apparently corresponds to a single species with great variation, regardless of the recognition of the populations of 4 northern distribution as a distinct taxon, and it would be better treated as an ochlospecies. Possibly ancient hybridization events were the origin of the current pattern of morphological variation.